How age and race affect the frequency, timing, and content of conversations about race with children. Issue 3 (19th May 2022) - Sullivan, Jessica; Wilton, Leigh; Apfelbaum, Evan P.
Abstract: Anti‐racist efforts require talking with children about race. The present work tested the predictors of U.S. adults' ( N  = 441; 52% female; 32% BIPOC participants; M age  = 35 years) conversations about race with children across two timepoints in 2019. Approximately 60% of adult participants talked to their children (3–12 years) about race during the preceding week; only 29% talked to other adults about race during the same period. This paper describes the content and predictors of conversations about race, revealing how conversations differ depending on the participant's race, a child's age, and whether the conversation occurs with children or another adult. These data have important implications for theorizing about when, why, and how adults actually talk about race with children and adults.